Implementation of Law Number 8 of 2016 on the Empowerment of People with Disabilities in Medan City - Rosmainda Butar Butar; Artha Lumban Tobing; Jonson Rajagukguk (Manunggal Halim Jaya, 2024)
Individuals with disabilities are citizens of the Republic of Indonesia who, as stipulated by the 1945 Constitution, are entitled to the same status, rights, obligations, and roles as all other citizens. In the realm of public services, they are afforded equal access across all sectors. This study aims to examine the implementation of Law Number 8 of 2016 concerning the empowerment of people with disabilities and to identify the specific programs initiated by the Medan City Government to enhance the empowerment of this community. The research adopts a qualitative approach, employing data collection and interview techniques. The findings reveal that, as of June 2023, there are 1,805 individuals with disabilities (based on data from 2022-2023). The study concludes that the implementation of Law Number 8 of 2016 has been effectively executed, with the Social Service playing a key role in administering the Medan City Government’s programs, including the distribution of assistance to individuals with disabilities.